Impact of Microplastic-Amended Soil on Seed Germination of Alfalfa (Medicago sativa) in a Controlled Environment - Abigail Tatum; Victoria Martin; Vanaja Kankarla (Agronomy)
Plastic pollution is a global concern due to its adverse environmental effects. Plastic production and consumption have continued to rise and are expected to double by 2050. Plastic disposal and degradation produce small particles of plastic—less than 5 mm—that can accumulate, infiltrate, or travel through soil, air, water, plants, and the environment. Healthy soil is a system in sync with good physical, chemical, and biological properties capable of supporting life. There is enough research to show the effects of microplastics (MPs) in aquatic environments; however, much is unclear about the effects of MPs on soil and food systems. To address this knowledge gap, two replicated germination experiments were conducted under a controlled environment in a germination chamber at the Water School Lab, Florida Gulf Coast University. The objective of this study was to determine the germination percentage (GP), mean germination time (MGT) and germination index (GI) of alfalfa seeds (Medicago sativa-VNS (variety not stated)) when germinated under two types of MP-treated soils: (1) fiber-fill plastic (FF) at 0.2% and 1% concentration and (2) plastic packaging (PP) at 0.2% and 1% concentration. The experiments were conducted in the germination chamber for 30 days at optimum germination temperatures of 25/18 °C day/night, with a 12-h photoperiod. The physical (texture, structure), chemical (pH, EC, moisture content (MC), and biological (microorganisms count) properties of the soil were analyzed in the laboratory to understand the impact of MPs on soil properties. In conclusion, our research shows MPs have minimal impacts on germination. Soil pH and MC (moisture content) decreased while EC increased across all treatments, and soil texture was negligibly altered. Microbial communities grew significantly across all treatments, showing that MPs can stimulate bacterial growth.